2009
DOI: 10.1111/j.1442-2050.2008.00896.x
|View full text |Cite
|
Sign up to set email alerts
|

Is the etiology of eosinophilic esophagitis in adults a response to allergy or reflux injury? Study of cellular proliferation markers

Abstract: Recent research suggests that allergy may be the key factor in the etiology of eosinophilic esophagitis (EE); however, historically, the condition was hypothesized as related to reflux injury to the esophageal mucosa. We studied this hypothesis by comparing markers of inflammation and cellular proliferation in EE and reflux esophagitis. Lower esophageal biopsies of adult patients with EE (n = 10), reflux esophagitis (n = 8), and normal controls (n = 13) were assessed quantitatively for the expression of the cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 47 publications
1
10
2
Order By: Relevance
“…showed that inhibiting 5‐LOX pathway with montelukast, a selective leukotriene D4 receptor antagonist, was ineffective to maintain steroid‐induced remission in adult EoE. Nonetheless, differing from our observations, Lewis et al . showed downregulation of COX‐2 expression in the esophageal biopsies of patients with EoE when compared with patients with gastroesophageal reflux disease and control subjects.…”
Section: Discussioncontrasting
confidence: 99%
“…showed that inhibiting 5‐LOX pathway with montelukast, a selective leukotriene D4 receptor antagonist, was ineffective to maintain steroid‐induced remission in adult EoE. Nonetheless, differing from our observations, Lewis et al . showed downregulation of COX‐2 expression in the esophageal biopsies of patients with EoE when compared with patients with gastroesophageal reflux disease and control subjects.…”
Section: Discussioncontrasting
confidence: 99%
“…61 Consistent with increased proliferation of the basal cells in response to allergen provocation rather than acid exposure, the biopsies from EE patients have down regulation of cyclooxygenase 2 (COX2). 62 Furthermore, esophageal biopsies from EE patients may have eosinophil surface layering and eosinophilic microabscesses, processes rarely associated with GERD. 63 In addition to eosinophils, esophageal biopsies from EE patients have increased levels of dendritic cells and mast cells, at levels generally higher than in GERD.…”
Section: Eosinophil Esophageal Levels and Histopathologymentioning
confidence: 99%
“…Although EoE may coexist with GORD, the conditions appear to be distinct, and although the exact relationship between the conditions remains controversial, there is currently little evidence to suggest an aetiological link 18. As demonstrated in all three of the presented patients, asthma and allergies are common (seen in 50%) 10.…”
Section: Discussionmentioning
confidence: 84%